2017
DOI: 10.5430/afr.v7n1p109
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Earnings-to-Price, Current Ratio, Profit Margin and Return: An Empirical Analysis on Istanbul Stock Exchange

Abstract: This paper aims to investigate the relationship between current ratio, earnings to price, net profit margin and stock returns in İstanbul Stock Exchange over the period 2008-2016 by employing panel data analysis. Due to the existence of heteroskedasticity, cross sectional dependence and autocorrelation in the sample data, robust estimators are used to estimate two-way fixed effects model is estimated. Both Parks-Kmenta and Beck-Katz methods are conducted to check whether the results are consistent or not. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
6
15
1
4
Order By: Relevance
“…But the results of the output test found no evidence of a relationship between the current ratio and stock return. The result of this study confirms previous studies by Öztürk and Karabulut (2018) and Stefano (2015) that stated the current ratio has no significant effect on stock return.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…But the results of the output test found no evidence of a relationship between the current ratio and stock return. The result of this study confirms previous studies by Öztürk and Karabulut (2018) and Stefano (2015) that stated the current ratio has no significant effect on stock return.…”
Section: Resultssupporting
confidence: 92%
“…Companies with liquid shares get more concern from investors on IDX, Even more, IDX has specifically categorized the company's shares in the LQ 45 index. Different result found by Öztürk and Karabulut (2018) and Stefano (2015) that stated CR has no significant on stock return. Dita and Murtaqi (2014) found debt to equity ratio has a positive and significant effect on stock return.…”
Section: Introductionmentioning
confidence: 62%
“…According to Kasmir (2012) and Subramanyam & Wild (2010), financial ratios are the results of comparison of numbers in the company's financial statements to be analyzed in order to get an overview of the conditions and trends of the company. The results of the study of Martani et al (2009) andEstuari (2010) concluded that the Current Ratio did not significantly affect stock returns, this is similar to the results of the Öztürk & Karabulut (2018) study. Meanwhile, Erdogan et al (2015) concluded that Current Ratio has a significant effect on stock returns.…”
Section: Financial Ratios That Influence Stock Returnssupporting
confidence: 77%
“…Meanwhile, Erdogan et al (2015) concluded that Current Ratio has a significant effect on stock returns. The results of Öztürk & Karabulut (2018), Estuari (2010) and Martani et al (2009) concluded that the Debt Equity Ratio had no significant effect on stock returns, while Erdogan et al (2015) concluded that these variables had a significant effect on stock returns. Martani et al (2009) study concluded that Total Asset Turnover had a significant effect on stock returns, which contradicts the results of research by Muhayatsyah (2012) and Asmi (2014) which stated that Total Asset Turnover did not significantly influence stock returns.…”
Section: Financial Ratios That Influence Stock Returnsmentioning
confidence: 99%
“…Earlier literature found that the inverse relationship between these dimensions was commonly observed by WCM and the gross benefit association (Karim et al, 2017;Samiloglu and Akgün, 2016;Chowdhury et al, 2018). Research findings show a negative and essential profitability effect of the debt-equity ratio (Chandra et al, 2016;Öztürk and Karabulut, 2018;Putri and Nasution, 2018). Companies' age and size influence the company's overall profitability (Goel and Sharma, 2015;Moussa, 2018).…”
Section: Literature Reviewmentioning
confidence: 92%